Troubleshooting & maintaining your PC all-in-one for dummies - Gookin, Dan. (Hoboken, NJ : Wiley Pub., 2011)
A guide to PC maintenance and repair, covering such topics as hardware, software, laptops, the Internet, networking, and Microsoft Windows 7, Vista, and XP.
Hardware. Let there be PC ; Birth pangs ; Death throes ; Mass storage issues ; Pain in the printer ; Seeing trouble ; Peripheralitis ; Deep inside the computer case -- Software. Windows gone AWOL ; Programs, processes, and services ; The safe mode chapter ; Putting the pep back into the PC ; User accounts ; Unexpected application situations ; Reporting for duty ; Recovery options ; Registry fixes -- Laptops. Laptop asleep, laptop awake, laptop dead ; A more usable laptop ; Out on the road ; Laptop maintenance -- Internet. Internet malaise ; Woes on the Web ; Email postage due ; Wicked software ; The file transfer chapter -- Networking. Network hardware help ; The soft side of networking ; Peer-to-peer networking ; Networking unplugged -- Maintenance. Backup, backup, backup ; Pampering the hard drive ; On schedule ; A time to clean.
"6 books in 1-- hardware, software, laptops, Internet, networking, maintenance"--Cover.
Includes index.
Keywords: Microsoft Windows (Computer file); Microcomputers -- Maintenance and repair; Microcomputers -- Upgrading; IBM-compatible computers -- Maintenance and repair; Laptop computers -- Maintenance and repair; Operating systems (Computers); Personal computers -- Maintenance and repair